Nature Conservation as Reflected in Hindu Theology and its Deviation in the Modern Days: A Discourse - Ojha, Rekha (ASEAN Journal of Religious and Cultural Research, 2022)
Nature conservation is considered as a key factor to save the essence of nature and protecting the species from destruction and it always includes the maintenance as well as restoration of the habitats which led to the enhancement of the eco system services to protect the biological diversity. It helps to maintain a healthy and functional eco system. The religion of Hinduism has always cared for the protection of nature which is clear from the Vedic principle of not harming the enviornment which include nature, water, flower, fruits etc. In Hinduism the earth is considered as the holy mother. In the opinion of the Vedic sages the body is composed of earth, water, fire, ether, air believing in the sanctity and purity of them. Rig Veda teaches us to respect and revere everything that the God has created. The central theme of Hinduism is that they believe that nature cannot be destroyed without human also being destroyed as we need the natural world in order to survive and every atman is a part of Brahman which is an uncreated, eternal, infite, transcendent and all-embracing principle containing in itself both being and non being and it is the sole reality which is the ultimate cause, foundation, source and goal of all existence. The theology of Hinduism believes that the world is made up of two things – spirit and matter. The spirit is considered as the thing that can neither be seen nor touched whereas matter could be seen and touched as well as can be destroyed. The Hindu sacred texts contain many references of divinity which are related to nature such as rivers, mountains, trees, animals, earth showing the caring of Hindu philosophy towards the conservation of nature. But in the modern days we have seen the people distancing themselves from the religious discourses of religious studies making it a fashion in the modern day which ultimately led to the people not caring for the nature conservation. As they were not unaware of the Sastric notations regarding the conservation of nature so they played a key role in the destruction of nature. Proper study of religious discourses from the childhood will enable the people to develop the ecofriendly mindset which will help in the conservation of nature in the modern days.